End-user involvement in developing and field testing an online contraceptive decision aid. (November 2018) - Hooiveld, Truus; Molenaar, Joyce M; van der Heijde, Claudia M; Meijman, Frans J; Groen, Theo P; Vonk, Peter
Objectives: Decision aids in the field of healthcare contribute to informed decision making. To increase the usefulness and effectiveness of decision aids, it is important to involve end-users in the development of these tools. This article reports on the development of an online contraceptive decision aid. Methods: An exploratory, qualitative study was conducted in the Netherlands between 2014 and 2016. The development process of the decision aid consisted of six steps and included a needs assessment and field test. Interviews were conducted with 17 female students. Results: The needs assessment provided information on the preferred content and structure of a contraceptive decision aid and guided the development of the online contraceptive decision aid prototype. Participants had an overall positive impression of the decision aid prototype during the field test. Minor revisions were made based on participants' feedback. Participants expected that the decision aid would positively contribute to decision making by increasing knowledge and awareness regarding the available contraceptive methods and their features and attributes, and by opening up to other options than the known methods. Conclusion: The developed contraceptive decision aid can contribute to better informed decision making and consultation preparation. Involving end-users in development seems valuable to adapt decision aids to specific needs and to identify in what way a decision aid influences decision making.